Desafios à pós-graduação em formação de professores na Universidade de Aveiro: das intenções às práticas - Maria Helena Sá Araújo e; Nilza Costa; Manuel Bernardo Canha; Isabel Alarcão (Universidade do Minho, 2002)
This study analyses the impact of the recent masters courses at the Department of Didactics and Educational Technology of the University of Aveiro, Portugal, on the professional development of the basic and secondary school teachers that have attended those courses, as well as on their peers teaching practice. The outcomes, obtained from a questionnaire applied to the master teachers, indicate that, from their view point, the courses have produced effects on the professional development of the teachers that have attended them. However, they also reveal the need to plan strategies that lead to the production of such impact on other subjects.